Evaluation of mass-rig systems for shaking table experiments (2012)
Shaking tables are experimental tools to assess the behavior of structures and nonstructural components under characteristic seismic vibrations. Because of the size and weight limitations of the tables, testing reduced-scale models or testing only the main structural components are normally necessary. In these cases, to comply with modeling requirements, large amount of extra-mass should be added to the specimen. This paper reviews and discusses the mass-rig systems for shaking table testing. The advantages and drawbacks of each system are critically compared. To avoid the risk of lateral instability of models and to maintain the weight of test specimens within table payload, external devices for transmitting the inertial forces to the models have become a preferred choice when tests are performed using small- or medium-size shaking tables.